(untitled) (Research, Society and Development, 2025)
The treatment of dental crown fractures has evolved with the introduction of minimally invasive techniques, with fragment reattachment being an effective alternative to restore both the function and aesthetics of the affected tooth. This approach, by preserving the original tooth structure, offers more natural and aesthetic results, especially in anterior teeth. However, the success of this procedure depends on a number of factors, including preservation of the fragment, adequate cavity preparation, the correct choice of adhesive materials and the reattachment technique used. In addition, the storage time of the fragment and adequate post-treatment management are crucial for the longevity of the treatment. This study seeks to explore these aspects, analyzing the reattachment techniques, the materials used and the clinical implications of the treatment of dental crown fractures. The literature highlights the importance of correct storage of fragments after trauma and the use of adhesion techniques that ensure the integrity of the restoration in the long term. In economic terms, reattachment presents itself as an affordable alternative compared to more invasive treatments, such as the fabrication of crowns. The analysis of the results showed that, when properly indicated and performed, reattaching offers an effective and low-cost solution for patients with crown fractures, maintaining dental aesthetics and occlusal function. The conclusion reinforces the relevance of this technique in the conservative treatment of dental fractures, highlighting the need for technical care and post-treatment follow-up for long-term success.